2010
DOI: 10.3136/fstr.16.87
|View full text |Cite
|
Sign up to set email alerts
|

Production of Exopolysaccharide by Lactobacillus plantarum and the Prebiotic Activity of the Exopolysaccharide

Abstract: Characteristics of an exopolysaccharide (EPS) produced by a mutant strain of Lactobacillus plantarum, strain 301102S, including yield from whey, monosaccharide analysis, and prebiotic activity, were investigated. The EPS production in whey was higher at 25℃ than at 30 and 37℃. The supplementation with yeast extract and glucose in whey gave a high EPS yield of 145 mg/L, and the EPS contained glucose and mannose (molar ratio, 1:2). Prebiotic activities of galactooligosaccharide, inulin and the EPS with 37 lactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 29 publications
1
25
1
2
Order By: Relevance
“…delbrueckii subsp. bulgaricus, 50-60 mg/l for Lactobacillus casei [52], and approximately 140 mg/l for Lactobacillus plantarum [45,53]. The highest recorded yields of hetero-EPS are 2775 mg/l for Lactobacillus rhamnosus RW-9595M [54] and 2500 mg/l for Lb.…”
Section: Hetero-epsmentioning
confidence: 82%
See 2 more Smart Citations
“…delbrueckii subsp. bulgaricus, 50-60 mg/l for Lactobacillus casei [52], and approximately 140 mg/l for Lactobacillus plantarum [45,53]. The highest recorded yields of hetero-EPS are 2775 mg/l for Lactobacillus rhamnosus RW-9595M [54] and 2500 mg/l for Lb.…”
Section: Hetero-epsmentioning
confidence: 82%
“…The effects of temperature on EPS production in whey were investigated in Lb. plantarum [53], and the yield was found to be higher at 25°C than at either 30°C or 37°C. Moreover, an inverse relationship was observed between EPS production per cell and the growth temperature for Lactobacillus sake [49], i.e.…”
Section: Hetero-epsmentioning
confidence: 92%
See 1 more Smart Citation
“…8 Also a lyophilized crude EPS from L. plantarum 301102S resulted with 1.6% protein content. 18 In addition, variations were observed in the EPS protein contents from L. rhamnosus while using galactose, lactose, glucose and maltose as carbon sources and the contents of total protein were found to be 3.88%, 2.82%, 2.59% and 6.82%, respectively. 11 The purity of the EPS is directly proportional to the protein contents present in the EPS.…”
Section: Total Protein Contentmentioning
confidence: 99%
“…with bacterial cells and the casein network, which is benefit to increase viscosity of yoghurt and avoid gel fracture and syneresis (Tsuda and Miyamoto, 2010). Prasanna et al (2013) found that porous structure could be formed in yoghurt fermented by EPSproducing LAB.…”
Section: Effect Of Yoghurt Starter On Eps Content and Viscosity Value Ofmentioning
confidence: 99%